Abnormal sleep blood pressure patterns are associated with the diffusion tensor imaging along the perivascular space index in cognitively impaired individuals - Buongiorno, Mariateresa; Sánchez-Benavides, Gonzalo; Caruana, Giovanni; Elias-Mas, Andrea; Artero, Cristina; Cullell, Natalia; Delgado, Pilar; Giraldo, Darly Milena; Marzal-Espí, Clara; Grau-Rivera, Oriol; de la Sierra, Alejandro; Delgado-Sanchez, Ariane; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionBlood pressure (BP) physiologically dips during sleep, and a lack of dipping is associated with adverse health outcomes and cognitive decline. Vascular pulsatility is the primary driver of glymphatic cerebrospinal fluid (CSF) transport, which removes metabolic waste products from the brain during sleep. We hypothesized that abnormal sleep BP patterns may affect glymphatic system health and that this relationship may result in lower diffusion tensor imaging along the perivascular space (DTI-ALPS) indices, a proposed neuroimaging index of glymphatic health.MethodsA total of 21 participants with mild-to-moderate cognitive impairment underwent 24-h ambulatory BP monitoring (ABPM), DTI-MRI, and Alzheimer's disease (AD) biomarker assessments. Of them, eight participants were classified as dippers (≥10%) and 13 as non-dippers (< 10%), using the sleep/awake systolic BP (SBP) percentage of change.ResultsWe found that the non-dippers had lower DTI-ALPS indices, even after adjusting for age and clinical stage (p = 0.013). Stiffness measures (pulse wave velocity) were negatively correlated with DTI-ALPS (r = −0.5), but the association disappeared after adjusting for age. Positive AD biomarkers were more frequently observed in the individuals who were classified as non-dippers for both systolic and diastolic BP (DBP), compared to the systolic and diastolic dippers (p = 0.041).DiscussionOur findings suggest that deviations from the physiological BP dipping sleep pattern may be related to poorer glymphatic function and increased AD pathology.